Implementation Of Education Quality Assurance System To Improve Internal Quality Assurance Department Of Family Welfare Education (PKK) Universitas Negeri Medan - Tresno Ingtyas, Fatma; Ampera, Dina; Wahidah, Siti; Jahidin, Ismail (CV. Inara, 2022)
Quality assurance is a series of related processes and systems for collecting, analyzing, and reporting data on the performance and quality of educators and education personnel, programs and institutions. The quality assurance process identifies aspects of achievement and priority for improvement, provides data as a basis for planning and decision making and helps build a culture of continuous improvement.This study aims to describe the implementation of the Internal Quality Assurance System (SPMI) as an effort to improve the quality of education in the PKK Department, Faculty of Engineering, Unimed. This study is a qualitative research with case study method. The research was conducted at the Department of Family Welfare Education (PKK) Faculty of Engineering, Unimed, with the subject of the Department of Quality Assurance Team (TPMJ PKK). Data collection techniques: direct observation, document and archive searches, and interviews. The results showed: (1) TPMJ policies and concepts in the form of academic documents and quality documents were prepared by TPMJ PKK; (2) TPMJ PKK as coordinator in planning and implementing learning in the PKK Department; (3) The implementation of the TPMJ is carried out by preparing a design in the form of the TPMJ PKK Cycle; (4) Obstacles faced: leadership commitment, number of auditors, TPMJ PKK activities become routine; (5) Steps to be taken: providing quality assurance experts, building a spirit of quality assurance; (6) Evaluation of TPMJ PKK Implementation is carried out every year; (7) Utilization of the results of TPMJ PKK implementation: building a culture of quality, accreditation; and (8) Development of TPMJ PKK implementation refers to the standard management of BAN PT.